2021
DOI: 10.3389/fvets.2021.663577
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary or Drinking Water Ruminococcus sp. Supplementation and/or Heat Stress on Growth, Histopathology, and Bursal Gene Expression of Broilers

Abstract: This research was conducted to evaluate the impact of dietary or drinking water Ruminococcus sp. supplementation and/or heat stress (HS) on the growth, serum biochemistry, tissue antioxidant, phagocytic assay, histopathology, and bursa gene expression of broilers. Day-old broiler chicks were allotted into six groups according to HS and/or Ruminococcus with or without enzyme supplementation. The first group was the control one, with a formulated diet and normal environmental temperature but without any suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Shortly after slaughter, small specimens from the thymus, spleen, kidneys, liver, and bursa of control and treated chicks were obtained. For fixation, the obtained samples were cleaned and soaked in 10% neutral buffered formalin liquid for 48 h. The paraffin-embedding technique was used to prepare the fixed samples (Saad et al 2021;Sato et al 1986, Wright andManos 1990). Several 4 mm in thick sections were cut and dyed with hematoxylin and eosin on a regular basis.…”
Section: Histopathological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly after slaughter, small specimens from the thymus, spleen, kidneys, liver, and bursa of control and treated chicks were obtained. For fixation, the obtained samples were cleaned and soaked in 10% neutral buffered formalin liquid for 48 h. The paraffin-embedding technique was used to prepare the fixed samples (Saad et al 2021;Sato et al 1986, Wright andManos 1990). Several 4 mm in thick sections were cut and dyed with hematoxylin and eosin on a regular basis.…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…A real-time polymerase chain reaction was used to evaluate the precise expression of inflammatory genes (IL-B1 and TNF-α) in muscle tissues (Dosoky et al 2021;Saad et al 2021). TRIzol reagent (Invitrogen/Life Technologies, Carlsbad, CA, USA) and NanoDrop for quantification were utilized for RNA extraction from ~ 100 mg muscle.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Butyrate-producing bacteria are considered as a group of beneficial bacteria that produce butytric acids through fermenting dietary fiber (Nylund et al, 2015). For example, the Gram-positive gut bacteria Ruminococcus, has been demonstrated to be quite enriched under health status but markedly depleted in numerous diseases including human motor neuron disease (Rowin et al, 2017;Saad et al, 2021). Besides, Bacillus clausii was verified to possess immunomodulatory activity, and play important role in regulating cell growth and differentiation, cell adhesion, signal transcription and transduction, vitamin production and protection of the intestine from genotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight experiments from eight studies (Hosseini-Vashan et al, 2016;Zhang et al, 2018;Chegini et al, 2019;He et al, 2019;Hirakawa et al, 2020;Abudabos et al, 2021;Saad et al, 2021) reported comparative immune organ masses between the Heat stress and Control groups. Notably, no heterogeneity was found, and there was a significant difference between the Heat stress and Control groups; thus, the random-effects model was applied (I 2 = 0%, P = 0.94, 1.00, 0.98) (Figures 2A-C).…”
Section: Analysis Of Studies That Investigated Immune Organ Mass and Study Biasesmentioning
confidence: 99%
“…A total of six experiments from six studies (Del Vesco et al, 2015;Awad et al, 2020;Beckford et al, 2020;Jiang et al, 2020;Saad et al, 2021;Zampiga et al, 2021) reported a comparative mortality rate between the Heat stress and Control groups. Significant heterogeneity was found, and a significant difference was found between the Heat stress and Control groups, indicating that the random-effects model is to be applied (I 2 = 63%, P =0.02) (Figure 6A).…”
Section: Analysis Of Studies That Investigated Broiler Mortality and Study Biasesmentioning
confidence: 99%